2005
DOI: 10.1378/chest.128.3.1324
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anatomic Manipulations on Pharyngeal Collapse

Abstract: Obstructive sleep apnea (OSA) is a common disease with important neurocognitive and cardiovascular sequelae. Existing therapies are unsatisfactory, leading investigators to seek alternative forms of anatomic manipulation to influence pharyngeal mechanics. We have developed a two-dimensional computational model of the normal human upper airway based on signal averaging of MRI. Using the finite element method, we can perform various anatomic perturbations on the structure in order to assess the impact of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…Berry et al (1999) reports muscle forces around 0.3N, supporting our estimate of forces less than 1N. In previous models lacking embedded muscles, the material of the soft palate has been modeled as a linear elastic material with Young’s modulus E = 25,000 Pa (Wang et al 2012; Liu et al 2007; Huang et al 2005). We also use a linear elastic model, but take a slightly softer E = 15,000 Pa, bearing in mind that the embedded muscles in our model will cause soft palate tissue to stiffen with activation (see, e.g., Cui et al 2008).…”
Section: Methodssupporting
confidence: 74%
“…Berry et al (1999) reports muscle forces around 0.3N, supporting our estimate of forces less than 1N. In previous models lacking embedded muscles, the material of the soft palate has been modeled as a linear elastic material with Young’s modulus E = 25,000 Pa (Wang et al 2012; Liu et al 2007; Huang et al 2005). We also use a linear elastic model, but take a slightly softer E = 15,000 Pa, bearing in mind that the embedded muscles in our model will cause soft palate tissue to stiffen with activation (see, e.g., Cui et al 2008).…”
Section: Methodssupporting
confidence: 74%
“…Previous modelling of the upper airways varies in complexity of geometry and material modelling. Two‐dimensional models investigate the pharyngeal mechanisms in the mid‐sagittal plane, however, they do not consider the influence of the lateral walls (Berry et al 1999, Huang et al 2007). Three‐dimensional models demonstrated that material modelling influences the response of the soft tissues when loads were applied (Pelteret et al 2014, Zhao et al 2013) but they are costly and are frequently based on single‐patient CT or MRI data.…”
Section: Methodsmentioning
confidence: 99%
“…The computed displacements resulting from supine to upright position presented in Table are compared to this value in order to have a guide on what material parameter set is most representative. Negative intraluminal pressure during inspiration narrows the airway and might lead to airway collapse . As the displacement of the soft palate is governed by air pressure with minimal influence of shear forces, the load on the soft palate during inspiration was modelled as a uniformly distributed negative pressure.…”
Section: Materials Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these limitations, as well as the conflicting data generated by clinical studies in predicting response to therapies, Huang et al [38,39 ] developed a finite element computer model of the upper airway to explore the effect of palatal resection, mandibular advancement and palatal stiffening [39 ]. This model was derived from signal averaged sagittal MRI scans of individuals with a normal upper airway.…”
Section: Imaging In the Evaluation Of Therapymentioning
confidence: 99%